Marsupial Frogs: Gastrotheca and allied genera. - Duellman, William E.; Duellman, William E. (Johns Hopkins University Press, Baltimore, USA, 2015)
This scientific masterpiece reveals many aspects of the lives of marsupial frogs and closely allied genera. Native to Central and South America, these amphibians differ from other frogs in that they protect their eggs after oviposition by either adhering them to the female’s back or placing them in a specialized dorsal pouch (thus the common name, marsupial frog). During mating, the male typically collects the eggs from the female with his feet—often one at a time and always out of water—fertilizes them, and then tucks them into the female’s pouch or attaches them to her back. In some species these eggs hatch as tadpoles, but most emerge as miniatures of the adults. Even among the tadpoles there is remarkable divergence, with some behaving in the typical manner (feeding and metamorphosing), whereas others forego all feeding until they metamorphose. In Marsupial Frogs, William E. Duellman’s synthesis of all that is known about the unique family Hemiphractidae is largely based on decades of his own careful laboratory and field study. He reveals the diversity of exotic color patterns and the frogs' geographic distributions by providing more than 200 photographs, illustrations, and maps. This exceptional tome should find its way into the libraries of serious herpetologists, tropical biologists, and developmental biologists. Included in this book are • A molecular phylogeny of the family Hemiphractidae• A thorough osteological analysis• A review of external morphological features• An overview of the evolution of reproductive modes• A biogeographic synthesis• Keys to genera and species• Diagnosis and thorough description of each species of marsupial frog• Colored physiographic maps depicting species distributions
Centro Jambatu - ID 1565